Los «papeles de Londres» y alertas sobre ingleses - Ximena Urbina Carrasco (Mélanges de la Casa de Velázquez, 2018)
There are three cases of «misgivings» of the Spanish crown due to the alleged imminence of English settlements on the southernmost coasts of Western Patagonia, a territory located between the province of Chiloé and the American border. These «misgivings», which gave rise to royal maritime reconnaissance orders that fell back on the governor of Chiloé, were provoked by the arrival at the Spanish court of «papeles de Londres» in which the ambassadors announced that England was preparing to take one or more ports from the South Sea. The cases allow us to analyze how these «papers» that generated «warnings» and dispatches constitute interesting cases to understand the circulation of information within the Spanish Empire, and between the latter and England, as well as the dynamics of the local (Chiloé) in relation to the regional (Chile, viceroyalty of Peru) and imperial (courts of Madrid and London), and vice versa. This was done by crossing information from Chilean, Spanish and English archives, with the intention of analyzing the history of the most radical Indian periphery through its link with modern European history.